KENDALAA PENINGKATAN KOMPETENSI PROFESIONAL GURU GEOGRAFI DI SMA NEGERI SE KOTA PADANG PANJANG - Irza cahaya; Khairani Khairani (JURNAL BUANA, 2020)
This research is ongoing in order to get constraints increasing the professional competence of geography teachers in (SMA) Negeri Padang City in terms of data (1) public identity, (2) self-development, (3) scientific publications and (4) innovative work of teachers. The research method uses quantitative descriptive methods. The population in this study was a geography teacher in six public high schools in Padang Panjang City. Data collection using a questionnaire (questionnaire). Based on the results of the study it can be concluded (1) The condition of the general identity of the geography teachers of the State High Schools in the City of Padang Panjang is quite good, because all the geography teachers of the State High Schools in the City of Padang Panajng have minimal education / last education having S1 and S2 which means they have met the minimum criteria, (2 ) Self-development of geography teachers in high schools throughout Padang Panjang City is still relatively low and there are still many who have not participated in self-development, (3) The scientific publications of geography teachers in Padang Panjang City are still very low, (4) Innovative work produced by geography teachers in The city of Padang Panjang does not exist at all.